Analysis of two domains with novel RNA-processing activities throws light on the complex evolution of ribosomal RNA biogenesis - Burroughs, A. Maxwell; Aravind, L. (Frontiers in Genetics, 2014)
Ribosomal biogenesis has been extensively investigated, especially to identify the elusive nucleases and cofactors involved in the complex rRNA processing events in eukaryotes. Large-scale screens in yeast identified two biochemically uncharacterized proteins, TSR3 and TSR4, as being key players required for rRNA maturation. Using multiple computational approaches we identify the conserved domains comprising these proteins and establish sequence and structural features providing novel insights regarding their roles. TSR3 is unified with the DTW domain into a novel superfamily of predicted enzymatic domains, with the balance of the available evidence pointing towards an RNase role with the archaeo-eukaryotic TSR3 proteins processing rRNA and the bacterial versions potentially processing tRNA. TSR4, its other eukaryotic homologs PDCD2/rp-8, PDCD2L, Zfrp8, and trus, the predominantly bacterial DUF1963 proteins, and other uncharacterized proteins are unified into a new domain superfamily, which arose from an ancient duplication event of a strand-swapped, dimer-forming all-beta unit. We identify conserved features mediating protein-protein interactions and propose a potential chaperone-like function. While contextual evidence supports a conserved role in ribosome biogenesis for the eukaryotic TSR4-related proteins, there is no evidence for such a role for the bacterial versions. Whereas TSR3-related proteins can be traced to the last universal common ancestor with a well-supported archaeo-eukaryotic branch, TSR4-related proteins of eukaryotes are derived from within the bacterial radiation of this superfamily, with archaea entirely lacking them. This provides evidence for “systems admixture”, which followed the early endosymbiotic event, playing a key role in the emergence of the uniquely eukaryotic ribosome biogenesis process.